INTERAKSI OBAT ANTIDIABETES DENGAN OBAT ANTITUBERKULOSIS (OAT) PADA PASIEN DIABETES MELLITUS TIPE 2 YANG TERINFEKSI TB PARU DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Auliafendri, Novycha; Sinaga, Alex Handani; Gea, Kiki Restini (Universitas Imelda Medan, 2024)
Diabetes is a medical condition that can worsen the severity of pulmonary tuberculosis (TB) infection. Combining Antidiabetic Drugs with Antituberculosis Drugs (OAT) in type 2 DM patients who have pulmonary TB can cause undesirable pharmacological interactions. The aim of this study is to explain the relationship between Antidiabetic Drugs and OAT. The research design used in this study is a cross-sectional observational design, with a focus on descriptive statistical analysis. The research sample consisted of 72 patients. Data collection was carried out retrospectively using medical records and doctor's prescription forms. The Medscape (Drug Interactions Checker) tool was used for drug interaction analysis, while SPSS (Statistical Product and Service Solution) 21.0 for Windows was used for data processing. Research findings revealed that the occurrence of drug interactions between Antidiabetic Drugs and OAT varied based on gender characteristics, with 56.9% observed in men and 43.1% in women. Pharmacodynamic interactions reached 25.5% based on the mechanism of action, while pharmacokinetic interactions reached 5.7%. The remaining 68.9% were classified as unknown interactions. In contrast, minor types of drug interactions reached 68.9% in terms of severity, while moderate types of interactions reached 31.1%, and there were no significant interactions. This study concludes that the combination of antidiabetic drugs and OAT mainly causes pharmacological interactions both in the pharmacodynamic and pharmacokinetic pathways, with varying levels of severity, ranging from minimal to moderate.